Inovasi Teknologi dalam Pemberdayaan Masyarakat: Membangun Kemandirian dan Kesejahteraan - Vivi Sylvia Purborini; Ida Bagus Suryanatha (PT Polstac Repositori Riset, 2025)
Technological innovation plays an important role in the current digital era, with a significant impact on various aspects of human life, including community empowerment. Technological transformation provides opportunities for society to improve the quality of life, reduce social inequality, and build economic independence. However, the implementation of technological innovation is not without challenges, especially in the context of diversity in access and acceptance in society. Research approaches must include elements of focused data collection, detailed analysis, and critical interpretation of findings related to the dynamics of technological innovation in society. Mixed methods, which combine qualitative and quantitative techniques, are often chosen in order to obtain a more comprehensive picture of the phenomenon under study. Community empowerment is a concept that emphasizes increasing the capacity of individuals and groups in communities to control their own lives. This approach focuses on developing local potential and independence, which can be done through active participation and collaborative efforts between various stakeholders. This research confirms that technological innovation plays a crucial role in empowering society by encouraging economic independence and improving prosperity. During the research, it was discovered that successful implementation of technology depends on accessibility and local adaptation. Even though there are challenges such as limited infrastructure and lack of public understanding, integration between various parties can accelerate technology adoption.